Methods for controlling natural regeneration of Japanese raisintree (Hovenia dulcis Thunb.) in Araucaria forest - Costa, Lucas Carvalho; Behling, Alexandre; Sanquetta, Carlos Roberto; Corte, Ana Paula Dalla; Mognon, Francelo (Iheringia, Série Botânica., 2018)
This study investigates methods for controlling Hovenia dulcis natural regeneration. The experiment was conducted in São João do Triunfo, PR, using randomized blocks with three treatments (control - A, root removal - B and base cut - C) and fi ve replications. Number of seedlings, saplings and small trees were recorded at the beginning, 60, 120 and 180 days after treatment. A high number of seedlings were observed, but over time mortality became evident regardless of treatment. Root removal reduced the number of seedlings when compared to base cut. Root removal diff ered statistically from the control and base cut treatments. Base cut did not diff er statistically from the control. Root system plays an important role in survival and regrowth of juveniles of the target species. Root removal prevents regrowth and survival based on natural regeneration. By its attributes, this species may be considered a relevant alien invasive tree in the Araucaria Forest.